(untitled) (Journal of the College of Basic Education, 2026)
Transportation in cities is a fundamental element that directly impacts urban activities and development in any city. This stems from the fact that movement on the street network can contribute to urban development due to increased population density and economic and service activities throughout the city. These streets, particularly in commercial areas, face several challenges related to traffic management due to the concentration of commercial activities (approximately 17%) and service establishments (15.1%), while public transportation accounts for only 8.3%. This necessitates an analytical study to identify existing problems and propose appropriate solutions to improve traffic flow and develop the urban environment in the Al-Ayadiyah district center. It is essential to highlight the current state of transportation in the Al-Ayadiyah district center and its relationship to land use from a functional perspective, thereby enhancing traffic efficiency and promoting sustainable development in the study area